Choosing The Optimum Conditions For The Determination Of Gallium Ion Using Eriochrome Red B Reagent - X.Sh.Bobojonov; X.U.Usmanova; Z.A.Smanova (Genius Journals, 2024)
In recent years, it is necessary to constantly monitor the amount of heavy and toxic metal ions from environmental objects. For this, there is a need for simple and fast methods of determining the metal ions being detected. In this work, work was carried out on the selection of optimal conditions for the determination of gallium ion using the eriochrome red V reagent using the fluorescent method.
Keywords: sorption; immobilization; heavy and toxic metal; fluorescence